Efficacy of microbial cell preparation in improving chronic constipation: a randomized, double-blind, placebo-controlled trial - Chin, K.F.; Jayasimhan, S.; Yap, N.Y.; Roest, Y.; Rajandram, R. (Elsevier, 2013)
Background & aims: Probiotics is an emerging therapeutic agent which may alleviate the symptoms of constipation. We evaluated the effectiveness of microbial cell preparation (Hexbio®) containing fructooligosaccharide,Bifidobacterium and Lactobacillus in improving stool frequency and symptoms of chronic constipation. Methods: A total of 120 constipated adults diagnosed using Rome III criteria were randomized and given either microbial cell preparation or placebo to be consumed twice daily. Follow-up was done after a 7-day intervention based on a questionnaire which includes an assessment of symptom profile and a stool diary. Results: During the intervention period, the stool frequency was higher (p = 0.001) in the treatment group. Subjects experienced less straining (p = 0.001) and sensation of incomplete evacuation (p < 0.001), as well as improved stool consistency (p < 0.001) compared to the placebo group. While a higher proportion of subjects in the treatment group had a reduction in anorectal blockage sensation and having to defecate by manual maneuvers, the differences were not statistically significant.